(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Quinoa (Chenopodium quinoa Wild., Amaranthaceous) is a stress-tolerant, grain-like food crop that for thousands of years has provided subsistence, nutrition, and medicine for indigenous Andean cultures. Quinoa includes a high content of photochemical that are good for wellbeing, including amino acids, fibre, polyunsaturated fatty acids, vitamins, minerals, spoons, phytosterols, phytoecdysteroids, phenolics, beta and lysine beanies. Numerous food products and nutraceutical products and processes have been produced from quinoa over the past 2 decades. In addition, 4 clinical studies have shown that supplementation with quinoa has significant, beneficial effects on human metabolic, cardiovascular, and gastrointestinal health. Within the research, agricultural and development sectors, however, vast challenges and opportunities remain to optimize the role of quinoa in promoting global human health and nutrition.